PENGARUH BEBAN KERJA, JOB INSECURITY DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION DI MEDIASI STRES KERJA SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada PT. Daehan Global Kabupaten Brebes) - Mar’atus Sholikhah; Ari Kristiana; Dwi Harini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the influence of workload, job insecurity and work environment on turnover intention mediated by work stress in the Cutting section of Building B PT. Daehan Global Brebes. This research is quantitative research using a descriptive approach. The population in this study was all employees in the Cutting Section of Building B PT Daehan Global, Brebes Regency, totaling 83 people. The sampling technique in this research used a non-probability sampling technique with saturated sampling. So 83 respondents were obtained. The data used is primary data in the form of a questionnaire instrument. Hypothesis testing uses multiple linear regression analysis using SPSS. The results of the research show that partial workload has a significant effect on turnover intention, partial job insecurity has a significant effect on turnover intention, partial work environment has a significant effect on turnover intention, partial workload has a significant effect on work stress, partial job insecurity has no effect significant influence on work stress, the work environment partially has a significant influence on work stress, work stress partially has a significant influence on turnover intention, workload, job insecurity and the work environment simultaneously there is a significant influence on turnover intention, workload, job insecurity and the environment Simultaneous work has a significant influence on work stress. Workload has a significant positive effect on turnover intention, mediated by work stress. Job insecurity has a significant positive effect on turnover intention, mediated by job stress. The work environment has a significant positive effect on turnover intention, mediated by employee work stress in the Cutting section of Building B PT. Daehan Global Brebes Regency.